The formulation of modern power configurations in the Keiskammahoek district of the Ciskei from c.1948 to the present - Westaway, Ashley Frank Hurford (Rhodes University, Faculty of Humanities, Department of History, 1993)
Much of the available documentation, and the multiple oral testimonies collected for this thesis agree that the most important changes that have occurred in Keiskammahoek district over the past half century resulted from the implementation of the government's conservationist policy known as betterment. The work is thus dominated by a wideranging look at betterment in Keiskammahoek The thesis is arranged chronologically, and each of the successive periods designated is analysed in terms of power. The first period considered is c.1920-c.1936; this was the time during which betterment policy was conceived. The key question that is posed here is why the policy was formed. Foucault's idea of power/knowledge features prominently in answering this question. For all of the remaining periods a conspicuously ,important power relation (unequal relationship) is chosen, and the analyses consist of plotting the histories of the various relations. The first of these periods is that which preceded the implementation of betterment in the district, i.e. c.1936-1960. Since multi-form resistance against betterment characterised this period, the power relation considered is that between the state and the various communities of Keiskammahoek. Next, attention is given to the actual implementation of betterment in the district. Because betterment affected locations in which land was held communally so differently from locations in which land was held under title, these two categories of location are analysed separately. In communal locations, a power relation spawned by betterment that has come to dominate life is that between village neighbours. In the other category of location, betterment has often further differentiated the power relation between title-deed holders and non title-deed holders. The thesis is not exclusively devoted to betterment. The 1970s saw many people being forcibly removed to Keiskammahoek. The final section of the work examines these events in relation to the changing economy of South Africa. In this section the power relation that is deemed important is that between the employed and unemployed The overall aim of the thesis then is to give an indication of the variety of forms or configurations of power that run through modernday Keiskammahoek.
Keywords: Keiskammahoek (South Africa) -- Social conditions; Keiskammahoek (South Africa) -- Economic conditions; Power (Social sciences) -- South Africa -- Keiskammahoek